THE ROLE OF BLOCKCHAIN TECHNOLOGY IN FACING REVOLUTION EDUCATION 4.0 - Agung Rizky; Shatya Silen; Desandio Ananda Putra (Program Studi Pendidikan Biologi, 2021)
Although several concepts for implementing education exaggerated using blockchain technology, t agreements which are allocated ledgers carefully and thoroughly. Blockchain technology, unlike databases that are processed by certain forces that provide policies in correctness of data through real-time implementation, Blockchain is a digital data storage system containing records that are connected via cryptography. Blockchain technology has now been used by various sectors, one of which is for transactions in cryptocurrencies such as Bitcoin. The benefit of the blockchain technology approach in education is that people who do not have knowledge of blockchain technology can benefit from blockchain technology, because a lot of the data generated by this sector is continuous from education to Bachelor. Blockchain, can be used as,